'The trial is owned by the team, not by an individual': a qualitative study exploring the role of teamwork in recruitment to randomised controlled trials in surgical oncology. Issue 1 (December 2016) - Strong, Sean; Paramasivan, Sangeetha; Mills, Nicola; Wilson, Caroline; Donovan, Jenny; Blazeby, Jane
Abstract Background Challenges exist in recruitment to trials involving interventions delivered by different clinical specialties. Collaboration is required between clinical specialty and research teams. The aim of this study was to explore how teamwork influences recruitment to a multicentre randomised controlled trial (RCT) involving interventions delivered by different clinical specialties. Methods Semi-structured interviews were conducted in three centres with a purposeful sample of members of the surgical, oncology and research teams recruiting to a feasibility RCT comparing definitive chemoradiotherapy with chemoradiotherapy and surgery for oesophageal squamous cell carcinoma. Interviews explored factors known to influence healthcare team effectiveness and were audio-recorded and thematically analysed. Sampling, data collection and analysis were undertaken iteratively and concurrently. Results Twenty-one interviews were conducted. Factors that influenced how team working impacted upon trial recruitment were centred on: (1) the multidisciplinary team (MDT) meeting, (2) leadership of the trial, and (3) the recruitment process. The weekly MDT meeting was reported as central to successful recruitment and formed the focus for creating a 'study team', bringing together clinical and research teams. Shared study leadership positively influenced healthcare professionals' willingness to participate. Interviewees perceived their clinical colleagues to have strong treatment preferences which led to scepticism regarding whether the treatments were being described to patients in a balanced manner. Conclusions This study has highlighted a number of aspects of team functioning that are important for recruitment to RCTs that span different clinical specialties. Understanding these issues will aid the production of guidance on team-relevant issues that should be considered in trial management and the development of interventions that will facilitate teamwork and improve recruitment to these challenging RCTs. Trial registration International Standard Randomised Controlled Trial Number (ISRCTN):ISRCTN89052791 .